2016
DOI: 10.1002/osp4.82
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal quality of life improvement in underserved rural youth with obesity

Abstract: SummaryObjectiveACT! (Actively Changing Together) is a family‐ and community‐based intervention targeting youth with obesity. The objective of this study was to establish the longitudinal impact on Health‐Related Quality of Life (HRQoL) as well as the relationship with anthropometric and demographic factors.MethodsYouth (n = 75) aged 8–14 years meeting criteria for overweight or obesity were referred to the programme. Twelve, 90‐min classes in English and Spanish were held at the YMCA. Demographics and anthrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
1
8
0
1
Order By: Relevance
“…The positive improvements observed via the SMU tool after this lifestyle and community-based intervention demonstrate that psychosocial health, particularly in regards to obesity-speci c domains, signi cantly improved in this group of youth. Results in this study of SMU paralleled those ndings from Peds-QL TM tool, a more widely-used tool, which was also used in this study and reported previously 8 . A systematic review 19 called for more interventions that target adolescence age groups, which our study included.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The positive improvements observed via the SMU tool after this lifestyle and community-based intervention demonstrate that psychosocial health, particularly in regards to obesity-speci c domains, signi cantly improved in this group of youth. Results in this study of SMU paralleled those ndings from Peds-QL TM tool, a more widely-used tool, which was also used in this study and reported previously 8 . A systematic review 19 called for more interventions that target adolescence age groups, which our study included.…”
Section: Discussionsupporting
confidence: 88%
“…15 The most widely employed instrument for assessing general HRQOL in youth, the Pediatric Quality of Life Inventory (PedsQL™), 16 was also employed in this study and reported previously. 8 The Child Health Utility (CHU9D) is a another generic pediatric quality of life instrument developed in the UK. 17 Alternatively, the Impact of Weight on Quality of Life (IWQOL)-Kids tool, like SMU, was also developed by the team at Cincinnati Children's Hospital.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers in the field of marriage and family therapy as well as human development, family studies, and medicine have noted the effectiveness of marriage and family therapy in working with clients regarding the matter of obesity [14][15][16][17]. Furthermore, a significant number of researchers have found that family-based interventions are effective for the treatment of obesity [18]. However, family-based interventions may or may not be conducted by marriage and family therapists [19].…”
Section: Obesity Treatment and Research In Marriage And Family Therapymentioning
confidence: 99%